Open And Distance Learning: Enhancing Legal Education for Postgraduate Students - Mohamed Yusoff, Zuryati (2022)
Seeking for knowledge is a never-ending process. While formal education or classroom based is not accessible to working adults, there is always chance for pursuit of knowledge for everyone with the help of highly advanced technologies nowadays. Open and Distance Learning (ODL) is a method of teaching and learning that offers open and flexible access to learning opportunities to anyone, anywhere, and at any time. Having these characteristics, the ODL approach promotes life long-learning process of gaining knowledge and learning new skills throughout. The purpose of this article is to enlighten the process of offering an ODL law program at the postgraduate level and how ODL characteristics benefitted potential learners to embark into this program. The challenges in terms of institution's readiness as well as instructor's readiness are also discussed in order to shed some lights on how to plan strategically and be prepared for the implementation of the ODL program for postgraduate students in particular at the School of Law, Universiti Utara Malaysia. The article concludes that while the process of implementing an ODL program is not an easy task, its benefit and advantages to potential learners outweigh challenges for academic institutions.